Unravelling physiological disorders in onion and garlic: critical assessment and bibliometric visualization - Kale, Rajiv B.; Khandagale, Kiran; Ramadas, Sendhil; Gavhane, Abhishek Dilip; Gedam, Pranjali; Mahajan, Vijay (Frontiers in Plant Science, 2024)
Onion and garlic are economically important vegetable crops cultivated worldwide. Numerous pests and diseases affect the quality and yield of these crops. In addition to diseases and pests, several physiological disorders affect onion and garlic. The physiological disorders are abnormalities caused by intercultural operations, nutrient management, environmental factors, genetic regulation, etc. These physiological disorders significantly affect the yield and quality of onion and garlic, leading to monetary losses to the farmers. The following physiological disorders are commonly reported in onion: premature bolting, sprouting in storage, watery scale, doubling/twins, basal plate split, and thick neck. Premature sprouting and rubberization are the main physiological anomalies observed in garlic. The present review described the symptoms of these physiological abnormalities, the factors responsible, and ways to avoid or minimise the occurrence of these abnormalities to subsequently reduce the losses of the growers. Further, we also performed bibliometric analysis using the SCOPUS database. This is the first review that describes the progress of research on physiological disorders in onion and garlic in detail, which will positively increase awareness about such important aspects of onion and garlic. Further, it will provide insight to researchers for developing innovative strategies, cultural practices, and varieties to control these physiological abnormalities of onion and garlic.